Elastic-plastic invariant of localized deformation autowaves; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Ploskov N. Nikita (2014, 2014)
Title screen